Internal Performance of Financial Accounting Auditors Cimanuk Cisanggarung Cirebon Center - Hartati, Wiwi; Suprihatin, Dina; Nurhawaeny, Endah (Jurnal Ekuisci, 2024)
An important issue contributing to the low completion rate of the Audit Results Report is the auditor's need for internal competence and understanding of the agency's accounting information system. This study aims to assess the internal performance of Financial Accounting Auditors at the Cimanuk Cisanggarung Cirebon Center. The study employs a quantitative descriptive approach to examine the impact of auditors' internal competence and accounting information systems on their internal performance. The study findings demonstrate that accounting information systems play a significant role and substantially impact knowledge. The statistical test F indicates that the auditor's internal competence and grasp of the accounting information system have a simultaneous and considerable impact on the auditor's internal performance. The findings of this study are consistent with the findings of a survey conducted by Anggraini (2008), which demonstrated that the internal competence of auditors has a tangible impact on both internal control and corporate performance. The internal performance of the auditor at the Cimanuk Cisanggarung Cirebon Center improves in direct proportion to the level of expertise and understanding they possess regarding the accounting information system.